Journey to the centre of the earth - Courtauld, Sarah; De Rold, Andrea Verne, Jules (Easton Press ; London, 2013)
When Axel deciphers an old parchment that describes a secret passage through a volcano to the centre of the earth, nothing will stop him and his eccentric uncle from embarking on a perilous, terrifying journey through the subterranean world